Eccentric connectivity index of chemical trees - Haoer, Raad Sehen; Mohd Atan, Kamel Ariffin; Khalaf, Abdul Jalil Manshad; Md. Said, Mohamad Rushdan; Hasni @ Abdullah, Roslan (AIP Publishing, 2016)
Let G = (V, E) be a simple connected molecular graph. In such a simple molecular graph, vertices and edges are depicted atoms and chemical bonds respectively; we refer to the sets of vertices by V (G) and edges by E (G). If d(u, v) be distance between two vertices u, v ∈ V(G) and can be defined as the length of a shortest path joining them. Then, the eccentricity connectivity index (ECI) of a molecular graph G is ξ(G) = ∑v∈V(G) d(v) ec(v), where d(v) is degree of a vertex v ∈ V(G). ec(v) is the length of a greatest path linking to another vertex of v. In this study, we focus the general formula for the eccentricity connectivity index (ECI) of some chemical trees as alkenes.